Addressing adenomyosis: Implications beyond we actually know - Kumar, Ganesh; Pachori, Purnima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hysterectomy is one of the commonest gynecological surgeries being performed in India for various pelvic pathologies like fibroid uterus, endometrial hyperplasia, dysfunctional uterine bleeding, etc. But pre-operative diagnosis of adenomyosis and making it an indication for hysterectomy is not as common as pathologists find it in histo-pathology of hysterectomized specimens. The aim of the study was to study the frequency of adenomyosis in comparison to leiomyoma as a uterine pathology in hysterectomized specimens and correlate them clinically. Methods: A retrospective comparative study was carried out on 1646 hysterectomy specimens, during January 2014 to December 2016, which showed either adenomyosis or leiomyoma or both. Clinical records of these cases were retrieved and histo-pathology was correlated to clinical presentations and pre-operative ultrasonography. Results: Of the 1646 specimens taken for comparision between adenomyosis and leiomyoma, 49% showed only adenomyosis, 37% only leiomyoma and 14% had dual pathology showing findings of both. The peri-menopausal age group (45-54 years) accounted for the maximum number of patients undergoing hysterectomy (37.12%). But adenomyosis was found maximum in 35 - 44 years age group (38.04%). The clinical presentations for these two pathologies were similar and maximum patients presented with abnormal uterine bleeding and pelvic pain. Ultrasonography was able to diagnose only 32% cases of adenomyosis pre-operatively whereas this figure was 87% for fibroids. Conclusions: Adenomyosis and leiomyoma both account for the most frequent findings in hysterectomy specimens. Fibroids are easily diagnosed pre-operatively, but adenomyosis needs to be diagnosed pre-operatively by high index of clinical suspicion and imaging techniques. Adenomyosis is not just a disease of middle age, it needs to be addressed for infertility, recurrent pregnancy loss (RPL), bad obstetric history, IVF failures and adherent placenta as well.